Reflexos da implantação do controle eletrônico de frequência na Universidade Federal de Goiás - Regional Goiânia: um estudo exploratório e descritivo - Dores Filho, Pedro Alberto das (2019)
In a context of political reforms, economic and financial crisis, criticism of the Public Administration, its managers and servants, nevertheless, Brazilian higher education suffers from such scenario, the process of reordering is exhausting, including radical changes that reflect on the organizational affected entities. Among the changes in management is the implementation of electronic frequency control (electronic point) as an auxiliary management tool. In Brazil, especially in educational institutions, this tool is being implemented in an obligatory manner, and its use in these institutions is not properly planned. Therefore, the present work aims to elaborate a proposal of intervention that consists in presenting a plan of action to implant the electronic point in the UFG aiming at the relation of this auxiliary managerial tool with the organizational management, being analyzed in the following aspects: management of people, organizational climate and culture, job performance and QVT, financial, IT and frequency control. Therefore, the present study intends to characterize UFG's HR policy, to identify national IFES and international institutions that have implemented the electronic point, to implement a pilot electronic point project at FCT / UFG and to apply a questionnaire to UFG / RG servers. Methodologically, the present research is denoted by an exploratory and descriptive study based on the search for bibliographical references inherent to the subject as well as pertinent legislation, seeking to analyze the reflexes of the coming implantation of the electronic point in the UFG. This exploratory study resulted in the description of an organizational environment not prepared for the implementation of the electronic point in the UFG, both by the management and the collaborators, resulting in the proposal of intervention presented, a plan of action with the best practices for the implantation of the point in the UFG. It also enabled positive perceptions to be perceived: agility, transparency, improved attendance and punctuality, and reduced costs; and negatives: feelings of injustice on the part of the servers, transfer of responsibility from the manager to the electronic point control system, limitations to fieldwork and worsening QVT and performance reduction. In short, this deployment should be planned and included in the PDI and PDTI of the UFG, with goals and objectives well delineated, better preventing the reflexes to come from this deployment.